Unveiling the complementariness of robotic tablet dispensing machines for elderly care: A bibliometric data analysis - Sunday Adewale Olaleye; Olaleye Esther Olubunmi; Berhanemeskel Weldegerima Atsbeha; Mulugeta Negash Wodaje (Elsevier, 2025)
This study conducts a bibliometric analysis of academic papers and conference proceedings related to tablet dispensers, medicine dispensers, and pill dispensers within the framework of Sustainable Development Goal 03: Good Health and Well-Being. The analysis spans literature published between 1997 and 2023. Utilizing the Web of Science database, the study employs keywords such as "tablet dispenser," "medicine dispenser," and "pill dispenser" to gather relevant English-language papers classified as Proceeding Papers or Articles. The inclusion and exclusion criteria filtered 79 initial records down to 40, focusing on articles pertinent to SDG 03. Data analysis was performed using the Biblioshiny App through RStudio, examining publication trends, authorship patterns, citation networks, and other bibliometric indicators. The findings reveal a steady increase in research output, moderate citation impact, extensive references, and collaborative authorship, with limited international collaboration. The study underscores the growing interest and research activity in robotic tablet dispensing machines for elderly care while highlighting areas for further global engagement.